PROSPECTS OF USING FINANCIAL TECHNOLOGIES BY BANKS OF DEVELOPMENT AS AN EXAMPLE OF ASIAN DEVELOPMENT BANK AND VNESHECONOMBANK OF RUSSIA - S. Matveevskii (Вестник университета)
The actual directions of development banks’ activity are determined. Financial technologies are actively used in the production and sale of financial services. Analysis of the materials of the Asian Development Bank, dedicated to the issues of using the digital economy, made it possible to identify the opportunities for the development banks of the fintech: identification and biometrics, rapid payments, large data analytics, blocking technology. Fintech will allow development banks to change the mechanism for planning and implementing projects, to increase the effectiveness of creating “chains” of value. Vnesheconombank’s projects related to fintech, in particular, the use of blocking technology in public procurement, are presented. At present, Vnesheconombank is successfully mastering Fintech and has good prospects for its use in practice.